Group Positive Psychotherapy Untuk Meningkatkan Kepuasan Hidup Pada Narapidana Di LP Kelas II A Kediri - Utami, Wahyu (Guidance and Counseling Study Program, Pattimura University, 2018)
This study aims to determine the influence of group positive psychotherapy on life satisfaction in inmates in IIA Kediri class. Subjects were 20 inmates living in prisons of IIA class in Kediri. Subjects selected by using purposive sampling technique which has low scores on life satisfaction scales with an age range of 20-39 years. This experimental research design uses Quasi experimental Pre-test-post-test control group design. Data analysis used is Different Test or t-Test and the technique used is paried Sample t-test. Data collection using the scale of Life satisfaction measuring tool using Satisfaction With life Scale (SWLS). The results showed that there was a difference of life satisfaction score in experimental group and control group that was obtained in control group with t-count value (1,000) less than t-table value (2,262) or significance value (0,343) more than alpha (0,050). In the experimental group the value of t-count (9,949) was more than the t-table value (2,262) or the significance value (0,000) less than the alpha (0.050).